C'était du spectacle!: l'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Keywords: Cabarets

Création d'un numéro de variétés suivie d'une réflexion sur l'évolution du travestisme à Montréal, de 1969 à 2000 - Gauthier, Ives (Université du Québec à Montréal, 2003)
Keywords: Théâtre

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Keywords: Chanson; Musique

From Kitchen to Carnegie Hall. Ethel Stark and the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
Keywords: Femmes; Montreal Women's Symphony; Musique

Re-viewing Reception: Criticism of Feminist Theatre in Montreal and Toronto, 1976 to Present - MacArthur, Laura Michelle (University of Toronto, 2014)
Keywords: Femmes; Féminisme; Théâtre

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Les éditions du remue-ménage, 2017)
Translators: _:n55267 Translators: _:n56475
Keywords: Femmes; Montreal Women's Symphony; Musicien; Musique

"Maple Leaf Rag" in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)
Keywords: Femmes; Musicien; Musique

Le rôle des femmes dans le développement des pratiques chorégraphiques expérimentales à Montréal dans la seconde moitié du XXe siècle - Fortin, Josiane (Études canadiennes / Canadian Studies, 2020)
Number: 88
Keywords: Danse; Femmes; Féminisme

Le Théâtre du Rideau Vert: un premier rôle dans l'histoire (2023)
OCLC: 1410824507
Keywords: Femmes; Théâtre du Rideau vert

Les représentations de la femme dans l’œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Keywords: Chanson; Musique

Penser la citoyenneté culturelle des femmes en musique au Québec : les trajectoires « ordinaires » d’Ella Charland (1896-1987) et de Léonie Claude (1893-1963) - Blais-Tremblay, Vanessa (Mens, 2023)
issued: 2023-23-00
Keywords: Femmes; Musique; Presse (La)

Du théâtre en famille. Les Marchand et le théâtre de société - Robert, Lucie (Les Cahiers des Dix, 2019)
Number: 73
Keywords: Journalistes; Marchand-Dandurand; Joséphine; Théâtre

Femmes de soir (théâtre); suivi de Contours: réflexion à partir du théâtre africain-américain - Amoni, Emmanuelle (Université du Québec à Montréal, 2000)
Keywords: Africains; Noirs; Théâtre

Un genre en construction: féminité et théâtre à la Congrégation Notre-Dame de Montréal - Plourde, Julie (Cahiers d'histoire, 2013)
issued: 2013-22-00
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Théâtre

Un genre en construction: Le théâtre à la Congrégation de Notre-Dame, 1850-1920 - Plourde, Julie (Université de Montréal, 2014)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Théâtre

La présence lesbienne dans le théâtre féministe québécois des années 1975-1985 chez Marie-Claire Blais, Pol Pelletier et Jovette Marchessault - Laillou Savona, Jeannelle (Voix et Images, 2010)
Number: 1
Keywords: Femmes; Féminisme; Théâtre

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Unviersité McGill, 2018)
Keywords: Femmes; Musicien; Musique; Noirs

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Number: 1
Keywords: Danse; Femmes; Histoire; Musicien; Musique

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
issued: 2021-21-00
Keywords: Bolduc; La; Chanson; Famille; Femmes

La place de l’art et de la culture au sein du féminisme québécois ou Jovette Marchessault d’hier et d’aujourd’hui - Michaud, Jacinthe (International Journal of Canadian Studies, 2023)
Keywords: Femmes; Féminisme; Théâtre; Écrivains

Femmes du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-21-00
Keywords: Barry; Robertine; Bélanger; Georgina (De Montreuil; Gaétane / Bélanger; Georgine); Circé-Côté; Éva; Danse; Femmes; Féminisme; Gérin-Lajoie; Marie; Journalistes; Langue; Écrivains; Élections

SAINT-JEAN, IDOLA - Lavigne, Marie; Stanton-Jean, Michèle (Dictionnaire biographique du Canada, 2003)

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens